A (Studies in Medieval and Early Modern Canon Law, Volume 6) pernicious sort of woman : quasi-religious women and canon lawyers in the later Middle Ages - Makowski, Elizabeth M., 1951- (Book collections on Project MUSE., 2005)
"Whether they were secular canonesses or beguines, tertiaries, or Sisters of the Common Life, quasi-religious women in the later Middle Ages lived their lives against a backdrop of struggle and insecurity resulting in large measure, from their ambivalent legal status. Because they lacked one or more of the canonical earmarks of religious women strictly speaking, they had to justify their unauthorized way of life and to defend themselves against association with those who had been branded unorthodox, unruly, or even heretical. Ambiguous legal status within the organized Church and the contests to which it gave rise are a constant theme in the historiography of quasi-religious women, yet there has been no full-scale study of what it meant at law to be a mulier religiosa." "This book provides a thorough examination of the writings of canon lawyers in the later Middle Ages as they come to terms, both in their academic work and also in their roles as judges and advisers, with women who were not, strictly speaking, religious, but who were popularly thought of as such. It studies the ways in which jurists strove to categorize these women and to clarify the sometimes ambivalent canons relating to their lives in the community. It assesses, among other things, the extent to which lawyers proved responsive to popular as well as learned notions of what constituted religious life for women when the interests of particular clients were at stake." "A useful supplement to books devoted to individual quasi-religious women or to specific manifestations of female lay piety, "A Pernicious Sort of Woman" will be of interest to historians of Christianity and specialists in the law and women's studies as well as anyone interested in the history of religious women."--Jacket.